Applying an Executive Sustainable Development Model to Executive Organizations based on Corporate Social Responsibility, and Green Management with Mediating Role of ISO 26000 and Comparing it - MINAEI, NASIM; POURKIANI, MASOUD; ZAYANDEHROODY, MOHSEN; SHEIKHI, AYYUB (The journal of contemporary issues in business and government, 2021)
Objective: Nowadays, insufficient attention to environmental issues and CSR in governmental organizations have undermined their performances and credibility. This research aims to comparatively study a sustainable development executive model based on CSR and green management with mediating role of ISO 26000 among executive organizations. Methods: This is a developmental-applied research with a comparative-inductive logic for data collection. This study uses a descriptive survey method. The statistical population consists of two samples of 32 experts and 360 managers, and deputies of provincial executive organizations. Data collection tools included a questionnaire of CSR, green management, and ISO 26000. Confirmatory factor analysis and structural equation modeling were used to analyze the data using SPSS and AMOS software. Results: The results indicate that social responsibility can predict green management in executive organizations. There is a significant relationship between these two variables with mediating role of ISO 26000. CSR has a positive and significant effect on green management and ISO 26000. Among the dimensions of social responsibility (leadership and intra-organizational processes), the dimensions of green management (leadership) and the dimensions of ISO 26000 (organizational governance) have the highest priorities. There is a significant relationship between the three levels of development in provinces in which this model was applied to their executive organizations. Originality/Value: Defining a sustainable development model and applying it to executive organization in Iran for the first time which adds to the dissemination of developmental research.